Determinan Financial Distress pada Industri Batu Bara Indonesia - Nurul Qomariah; Khristina Yunita; Nella Yantiana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The purpose of this study is to test and analyze the effect of profitability, liquidity and leverage on financial distress with the interaction of the size of the Public Accounting Firm (KAP) as a moderating variable. The object of this study is the coal industry listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. Sampling using purposive sampling method and obtained 56 samples. This research method uses a quantitative approach with the help of Eviews 12 software. The research variables consist of profitability, liquidity, leverage, size of the Public Accounting Firm (KAP), and financial distress as measured using the Interest Coverage Ratio (ICR). The study results show that profitability contributes positively to financial distress, liquidity and leverage have no effect on financial distress, KAP size does not moderate the relationship between profitability liquidity, and leverage on financial distress. These findings suggest that profitability is a major factor in maintaining the financial stability of companies, especially in the coal sector which is vulnerable to market volatility. Therefore, maintaining profit is an important step in reducing the risk of financial distress.